Las políticas de descentralización de los servicios públicos municipales: análisis desde enfoques institucionales de segunda generación. - Amaya Ventura, María de Lourdes (El Colegio de México A.C., 2014)
This paper exemplifies the application of institutional analysis to the policy of decentralizing urban services. The example taken is water management in Mexico; empirical evidence of three types of institutionalism is examined: rational choice, organizational and historical. Taking up the model of institutional change proposed by Campbell and Pedersen, exponents of second-generation institutionalism, the decentralization of water management is analyzed on the basis of the problem that causes the change, the underlying conditions and the mechanisms it adopts. Finally, a model of analysis of institutional change is proposed for water management together with a series of reflections on how institutional paradigms may be combined in the study of specific cases.